REVIEW OF LIFE SAFETY EQUIPMENT TOOL AT KMP. PERMATA LESTARI II KAYANGAN TRACK - POTO TANO WEST NUSA TENGGARA PROVINCE - Budi Mantoro; Muhammad Khairani; AJi Maspanji Putra Mataram (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2021)
Kayangan Crossing Port is organized and managed by PT. ASDP Indonesia Ferry (Persero), this crossing port serves 1 track with 23 Ro-Ro type ships (roll on - roll off) in operation. The high level of demand for crossing services, encourages the government to pay attention to all components related to crossing transportation, such as safety aspects that are one of the important components in crossing transportation. Including life safety equipment on board the ship as a form of anticipation in the event of an emergency. The method used in this study was carried out by comparing the existing state with the expected circumstances under the International Safety Of Life at Sea (SOLAS) Regulation of 1974 Chapter III amendment year 2014. The author tried to analyze the problems that will later be drawn to be a solution or solution to the problem in an effort to increase supervision of the number and condition of passenger safety equipment on board ships operating at the pontoon dock at Gilimanuk Crossing Port of Bali Province.